Energy policy of India: Development trajectories and climate action - Rajnish Saryal (Social Sciences and Humanities Open)
The climate crisis forced countries of the world to rethink their energy security. The growing international concerns for unchecked fossil fuel use pressured developing countries like India, one of the world's fastest-growing economies, to reconsider their energy policies. India, the third-largest emitter of greenhouse gases, became a key player in climate negotiations to influence the global efforts for a clean energy transition. The article used the explorative method of literature analysis to explore whether or to what extent India's energy policy successfully redefines development trajectories while fulfilling climate commitments under the Paris Agreement. The results showed that India made remarkable progress in clean energy transition by promoting renewable energy. Still, it lacks the ability to streamline green financing into the policy framework to become a developed state by 2047 and a carbon-neutral economy by 2070. The article concluded that a comprehensive energy policy, with the right level of energy mix, is essential for India to achieve development goals while addressing the energy sector challenges and climate change.